2014
DOI: 10.1021/es404147c
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Transformation and Distribution Across a Polyvinyl Chloride (PVC) Production Line in China

Abstract: The production of polyvinyl chloride (PVC) via the calcium carbide process utilizes a catalyst containing large amounts of mercury (Hg) and is therefore one of the most important sources of anthropogenic Hg in China. To measure the emission of Hg from PVC production, we established a flowchart for the calcium carbide process, for which we quantified the Hg content of the material/product at each step. Results indicated that 71.5% of the total Hg (Hg(T)) was lost from the catalyst, most of which was recovered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…However, knowledge gaps in the emission estimates in China remain for the source categories whose emission factors have not been verified. Hg emissions related to the production, consumption and recycling of Hg in artisanal mercury and gold production, polyvinyl chloride (PVC) production, mercury batteries, mercury sphygmomanometers, and mercury thermometers, are potentially large Hg sources in China but have not been well evaluated Ren et al, 2014;Minschwaner et al, 2010). Other reasons causing earlier underestimation include natural emissions and conversion of GOM and/or PBM to GEM in the stack or in the plume during transit (Jaffe et al, 2005).…”
Section: Inferences On Hg Emissions In Chinamentioning
confidence: 99%
“…However, knowledge gaps in the emission estimates in China remain for the source categories whose emission factors have not been verified. Hg emissions related to the production, consumption and recycling of Hg in artisanal mercury and gold production, polyvinyl chloride (PVC) production, mercury batteries, mercury sphygmomanometers, and mercury thermometers, are potentially large Hg sources in China but have not been well evaluated Ren et al, 2014;Minschwaner et al, 2010). Other reasons causing earlier underestimation include natural emissions and conversion of GOM and/or PBM to GEM in the stack or in the plume during transit (Jaffe et al, 2005).…”
Section: Inferences On Hg Emissions In Chinamentioning
confidence: 99%
“…Mercury chloride catalyst waste (HgCl 2 ) spontaneously forms through catalyst erosion in the presence of hydrogen chloride and acetylene during PVC manufacturing . It can further transform into different chemical species of mercury . Although PVC is produced from acetylene without direct involvement of calcium carbide, the manufacturing processes are frequently combined to facilitate their optimization .…”
Section: Sustainable Access Usage and Recycling Of Calcium Carbidementioning
confidence: 99%
“…The production of polyvinyl chloride (PVC) with the calcium carbide process utilizes a catalyst containing large amounts of mercury. Ren et al (2014) conducted on-site measurements in a PVC production line and found that 71.5 % of the total mercury was lost from the catalyst, most of which was recovered by the mercury remover, accounting for 46 % of the total mercury. The total mercury emitted to the atmosphere only accounted for less than 1 % of the total mercury in the catalyst.…”
Section: Mercury Speciation and Transformation In Flue Gas From Pvc Pmentioning
confidence: 99%